An Appearance of the Collective Unconscious in a Military Mental Health Clinic. (3rd April 2017) - Christian, Thomas M.
Abstract : An active-duty patient in a military mental health setting encounters an endogenous psychological image by way of deep psychotherapeutic work. The image represents both a healing agent for the patient and a symbol of Jung's descriptions of the unio mystica . In this way the patient's image serves as a doorway to comprehending deeper psychological realities. Interpretations and meanings are discussed vis-à-vis the patient's trajectory toward greater balance and overall mental health.